2003
DOI: 10.1074/jbc.m206579200
|View full text |Cite
|
Sign up to set email alerts
|

PYK2 Autophosphorylation, but Not Kinase Activity, Is Necessary for Adhesion-induced Association with c-Src, Osteoclast Spreading, and Bone Resorption

Abstract: Proline-rich tyrosine kinase 2 (PYK2) is the main adhesion-induced kinase in bone-resorbing osteoclasts. Previous studies have shown that ligation of ␣ v ␤ 3 integrin in osteoclasts induces c-Src-dependent tyrosine phosphorylation and PYK2 activation, leading to cytoskeletal rearrangement, migration, and polarization of these cells. In this study, we examined the role of PYK2 kinase activity and its major autophosphorylation site in adhesion-dependent signaling and cytoskeletal organization during osteoclast s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 45 publications
9
91
0
1
Order By: Relevance
“…Expression of Pyk2 Y402F mutant or antisense RNAs was reported to inhibit osteoclast migration in response to M-CSF and their spreading onto vitronectin (Duong et al, 2001, Lakkakorpi et al, 2003. Consistently, we found that Wrch1 interfered with Pyk2 Y402 phosphorylation and inhibited adhesion to vitronectin and migration in response to M-CSF.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Expression of Pyk2 Y402F mutant or antisense RNAs was reported to inhibit osteoclast migration in response to M-CSF and their spreading onto vitronectin (Duong et al, 2001, Lakkakorpi et al, 2003. Consistently, we found that Wrch1 interfered with Pyk2 Y402 phosphorylation and inhibited adhesion to vitronectin and migration in response to M-CSF.…”
Section: Discussionsupporting
confidence: 74%
“…It is also necessary for osteoclast bone resorbing activity (Zou et al, 2007). Integrin αvß3 interaction with extracellular matrix proteins activates multiple signaling pathways, in particular phosphorylation cascades triggered by the tyrosine kinases Src and Pyk2 (Lakkakorpi et al, 2003, Miyazaki et al, 2004, to regulate podosome dynamics and organization, sealing zone formation and bone resorption (Destaing et al, 2008, Gil-Henn et al, 2007, Shyu et al, 2007. Much less is known about the importance of integrin signaling during osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While elevated ERK/MAPK, p38/MAPK and c-Src activities are correlated with increased PYK2 activity and enhanced adhesion in C-81 as well as PYK2 cDNA-transfected C-33 cells (Supplementary Figure 1A and 2), only ERK/ MAPK activity was consistently reduced by expressing the Y402F or the K457A-PYK2 mutants in C-81 cells, correlated with a decreased adhesion (Figure 6, Supplementary Figure 1B). Interestingly, those K457A mutant proteins still exhibit functional Y402 which led to c-Src activation, as described in osteoclasts-like cells (Lakkakorpi et al, 2003). Thus, PYK2 activates ERK/MAPK and c-Src by differential mechanisms, in which ERK/ MAPK activation depends on both Y402 phosphorylation and kinase activity, while c-Src activation only requires Y402 phosphorylation.…”
Section: Discussionmentioning
confidence: 69%